Applying Board Race Game to Increase Students’ Vocabulary Mastery in Uttayan Suksa Krabi School, Thailand - Octaviani, Risa; Handayani, Ika; Hamer, Welliam (Journal of English Education Studies, 2019)
The aim of this research was to know the increase of students’ vocabulary mastery by using board race game for fifth grade students of Uttayan Suksa Krabi School, Thailand in the academic year 2018/2019. The method used in this research was collaborative classroom action research. The researchers conducted this research from December 2018 until March 2019 in Uttayan Suksa Krabi School, Thailand. In collecting the data, the researchers used observation, test, and documentation. The tests were given in pre-test, post-test 1 and post- test 2. The researchers analyzed the average score of each test to find out the increase of students’ vocabulary mastery after the action was conducted. After the researchers have conducted the action, the students’ vocabulary mastery has increased optimally. It could be seen from the score of pre-test that showed 55.3, post-test 1 was 68.6, and post-test 2 was 85.6. After applying the action, the researchers were able to solve the problem in increasing students’ vocabulary mastery. The students were able to pronounce, memorize and understand the words based on the context. By using Board Race game in teaching vocabulary, the students could easily understand and memorize the spelling of the new vocabulary. In the teaching process, when the researcher as teacher used game, the students were enthusiastic and enjoyed during teaching learning process. It can be concluded that board race game can increase students’ vocabulary mastery. It is suggested to use board race game as the alternative media in teaching learning English.